Estudio de prefactibilidad para la instalación de una planta procesadora de shampoo a base de saponina de quinua como tensoactivo natural - Loo Salinas, Alejandra (2021)
In the present investigation, the economic, commercial, social, technological and environmental feasibility was evaluated for the installation of a shampoo plant based on quinoa saponin as a natural surfactant, in order to be able to satisfy the basic hair care needs of our market, by means of a product that uses a natural by-product of quinoa as raw material, being friendly to the human scalp and the environment. Firstly, a market study was carried out, obtaining a demand for the last year of the project's useful life of 9,782 boxes; each one containing 12 bottles of shampoo of 500 ml. Then we determined the marketing strategy to be used, focusing on one of differentiation of our product based on quality. Later, a plant location study was carried out using the "Factor Ranking" and "Brown & Gibson" methods, concluding that the best location to establish our plant is the district of Lurin, Lima. Likewise, a calculation was made to determine the capacity of the plant based on our production lot, finding a value of 47,174 boxes per year; this being less than our Technology size which corresponds to 62,122 boxes, giving us an opportunity for future expansion. For the engineering section of the project, we described the production process, the machines to be used, the design of the facilities, the quality standards related to the product, the environmental impact generated, the safety and protection measures, and the layout of the plant. With the analysis carried out, a plant of 1030.84 m2 was obtained. Finally, the economic evaluation of the project was carried out with an investment of S/. 664,863.43; obtaining an economic NPV of S/. 514,840.10, an IRR of 46% and a recovery period of 3.54 years. On the other hand, for the financial evaluation a NPV of S/. S/. 592,972.92, an IRR of 61% and a recovery period of 2.18 years were obtained. Therefore, it was decided to seek financial support from Banco Continental to obtain more viable indicators for the development of the company.